Electrochemical behavior of AISI 302 austenitic stainless steel in coal chemical high‐salt wastewater. Issue 11 (12th July 2021) - Yang, Guangming; Wang, Weibing; Ren, Yongsheng; Ma, Yulong
Abstract: In this study, the effect of grain size and grain boundary characteristic distribution on the corrosion resistance of AISI 302 austenitic stainless steel in simulated coal chemical high‐salt wastewater was evaluated by electrochemical impedance spectroscopy and potentiodynamic polarization measurements. The grain size of the heat‐treated sample is significantly increased and contains a greater fraction of high‐angle grain boundaries (HAGBs) and twin content. As the heat treatment temperature and time increase, the passivation current density increases, which makes the passive film more susceptible to attack. The coarse‐grained microstructure has exhibited worse pitting resistance due to its higher fraction of the HAGBs. Abstract : The grain size of the heat‐treated sample is significantly increased and contains a greater fraction of high‐angle grain boundaries and twin content. As the heat treatment temperature and time increase, the passivation current density increases, which makes the passive film more susceptible to attack. The coarse‐grained microstructure has exhibited worse pitting resistance due to its higher surface area of the high‐angle grain boundaries.